1990
DOI: 10.2172/138357
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary calculations of release rates of Tc-99, I-129, and Np-237 from spent fuel in a potential repository in tuff

Abstract: Regents of the University of California, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, process, or service by its trade name, trademark, manufacturer, or other,cise, does not necessarily constitute or imply its en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…TSPA-1991 assumed 2.1 metric tons of heavy metal per container, based on Apted et al (1990). The only distinction between the two groups was the assumed burnup value which was 33,000 megawatt-days per metric ton of heavy metal (MWd/MTHM) for PWR, and 27,500 MWd/MTHM for BWR.…”
Section: Tspa-1991 Approach To Waste Packagementioning
confidence: 99%
See 2 more Smart Citations
“…TSPA-1991 assumed 2.1 metric tons of heavy metal per container, based on Apted et al (1990). The only distinction between the two groups was the assumed burnup value which was 33,000 megawatt-days per metric ton of heavy metal (MWd/MTHM) for PWR, and 27,500 MWd/MTHM for BWR.…”
Section: Tspa-1991 Approach To Waste Packagementioning
confidence: 99%
“…The matrix alteration is assumed to proceed at a certain rate, but only part of the waste is contacted by water and is releasing its waste to the water. The TSPA-1991 matrix alteration rate upper bound was based on laboratory experiments of spent fuel leaching (Apted et al, 1990). The lower bound was arbitrarily selected as 20 times lov,er to reflect the uncertainty in the parameter (Barnard et al, 1992).…”
Section: Tspa-1991 Approach To Waste Packagementioning
confidence: 99%
See 1 more Smart Citation
“…conservatively assumed, based on other analyses for Yucca Mountain (Sadeghi 1990;Apted 1990), that the void region between the waste container and tuff host rock is filled with a matrix of crushed tuff with a 50% porosity. This (a) For elements with more than one long-lived isotope,an "isotopic solubility"is equal to the elemental solubilitytimes the mass fraction of that particularisotope at 1000 years after emplacement.…”
Section: Repository Datamentioning
confidence: 99%
“…Waste packages from aqueous processing of LWR spent fuel For tile spent-fuel waste package[Apted et al 1991], as well as each of the waste packages identified inTables 1, 2and 3, the inventories of the tracked radionuclides are given, at 10, 100, 300, 1000, 5000 and 10,000 years after emplacement, in Tables 4 through 15. This data are the basis for calculating release rates and estimating the impact of inadvertent human intrusion.…”
mentioning
confidence: 99%